Necessidades de formação de professoras principiantes da educação infantil/pré-escola - Campos, Rebeca Ramos (2014)
This work arose from our concerns with the issues of teacher training for early childhood education. From the difficulties encountered as a novice teacher in elementary, we deem important to research training needs of these professionals. Thus, we define the objective of this research to investigate the training needs of novice teachers teaching Early Childhood Education/Elementary school. Our work fits in Educational Research Qualitative Approach, and its construction procedures of the semistructured interview data and document analysis. Our empirical field was made up of schools in the metropolitan region of Natal / RN, offering kindergarten / elementary school. The subjects are five teachers who act as holder of the elementary school class and have 0-3 years of teaching practice, characterizing the second Huberman (2007) as novice teachers. Data analysis, based on principles of content analysis, three themes emerged: Beginner Teaching Professor in Early Childhood Education / Preschool; Reasons explaining the difficulties Faculty / Formative Needs Teaching and Training in Early Childhood Education / Elementary school, from the Training Needs Analysis, with their respective categories, subcategories, contributing to our understanding of the subject matter. The entry into the profession is marked by mixed feelings of euphoria and fear, where there seems to be a "clash" with reality. The difficulties are related to the planning / execution of activities, meet the individual needs of learning and assessment of children. As a strategy to overcome the difficulties the teachers exercise the action-reflection-action in their practices and seek continuous updates in the theoretical and methodological framework of early childhood education. The reasons that define these difficulties may be related to the teacher, school, family, and students of these institutions. In experiencing these difficulties has outlined the need for teacher training, among which stand out studies on ethics in teaching with children, the concept of children and their childhoods, peculiarities of teaching / learning in preschool, toys and legal determinations on early childhood education, multi-language and expressions in early childhood education, specific content areas of knowledge, among others. Furthermore, studies on the theoretical as Piaget, Vigotsky, Maria Carmen Barbosa and Emily Smith. For these professionals to be a professional early childhood education is: like children, be patient and careful, have specific theoretical and practical training for teachers in kindergarten, being able to improvise with seriousness and competence and get updates on continuing education. The surveys, together with the authors and teachers, to confirm our understanding that the training needs of beginners may be related to shortcomings in the initial and continuing education